Plan de negocios para la creación de una hostería agroturística, en naranjal provincia del Guayas - Salazar Salazar, Christian Harold (2015)
This research has been developed to determine the commercial viability and financial feasibility of the project Creating a farm holiday inn located in the Orangery Canton, on the trail of cocoa because the entrepreneur and his family have land in the area and have been dedicated to the cocoa industry. When analyzing the foreign market for both the tourist industry and the cocoa has been a growth in recent years there Mipro support for both, plus government support and society is growing and encourages the farm; Moreover, tourists looking for places that allow them to diversify their experience in the country. When the market study has shown a high demand and acceptance of such projects by the proximity and travel experience that is offered to provide all the properties of cocoa and chocolate at every visit, plus complementary products was determined such as the spa, the Chocolate Factory, bar, restaurant, plus hosting service; although demand is high only considered 40% annual occupancy due to the seasonality of it…